Kopiah dan Sarung Identitas Pesantren : Studi Historis Tentang Perlawan Pesantren Terhadap Kebudayaan Eropa (LPTNU Sumenep, 2023)
This article analyzes the tradition of wearing a skullcap and sarong in the pesantren environment so that it becomes the identity of the santri. It even became a penetration of European clothing fashions brought by the colonizers to the archipelago. To unravel the puzzle, the author uses the historiography method with a heuristic approach or data collection, either in the form of documentation, archives, books, articles, theses and so on, so as to capture as many historical traces as possible. After testing the authenticity of the data and linking it with other data, it is confirmed that the skullcap and sarong are pesantren traditions whose functions are as worship clothes, religious events, santri identity, community identity, symbols of difference between natives and invaders or resistance in the realm of the struggle for independence. Wearing these two symbols signifies zuhudan about the knowledge that students get at the pesantren.